Atención al cliente en la cooperativa de ahorro y crédito Coac Credil limitada en el cantón Salcedo periodo 2022-2023 - Inlago Cabascango, Jazmín Dayana (2023)
This research report studies the internal and external customer service of the COAC CREDIL Limited Savings and Credit Cooperative in the Salcedo canton. The general objective of this work is to present a tool that helps improve customer service and attention. For this, we have taken the use of the Servqual model as a reference, which will allow us to measure the quality of service through expectations and perceptions of customers in five dimensions that are improved according to the need of the users.